Empowering Communities Through Islamic Funeral Care Education in Sumur Bandung Hamlet - Dadan Mardani; Lentera Asih (World Journal of Islamic Learning and Teaching, 2025)
Funeral care is an essential religious obligation in Islam, yet many communities lack adequate knowledge and experience in performing proper funeral rites. This community service project aimed to provide education and practical training on caring for the deceased following Islamic teachings. Conducted in Sumur Bandung Hamlet, Haurgeulis District, Indramayu Regency, on January 31, 2025, the training involved 40 participants, including 10 men and 30 women. The methods used included lectures to deliver theoretical knowledge, demonstrations to show correct procedures, and hands-on practice to enhance participants’ skills. The results indicated a significant improvement in participants’ understanding and abilities in funeral care. Prior to the training, only 13 participants had prior experience or training, while 27 had never been exposed to funeral care procedures. By the end of the session, all participants had gained practical experience and demonstrated improved knowledge. This initiative not only enhanced religious literacy but also fostered social awareness and solidarity within the community. It is recommended that similar training programs be conducted regularly to ensure community readiness in fulfilling this religious duty.